2024
DOI: 10.1161/circulationaha.123.066659
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between End-Tidal Carbon Dioxide During Pediatric Cardiopulmonary Resuscitation, Cardiopulmonary Resuscitation Quality, and Survival

Ryan W. Morgan,
Ron W. Reeder,
Dieter Bender
et al.

Abstract: Background: Supported by laboratory and clinical investigations of adult cardiopulmonary arrest, resuscitation guidelines recommend monitoring end-tidal carbon dioxide (ETCO2) as an indicator of CPR quality but note that "specific values to guide therapy have not been established in children." Methods: This prospective observational cohort study was an NHLBI-funded ancillary study of children in the ICU-RESUS citation trial (NCT0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Fourth, this study cannot control for unrecorded variables, such as the quality of bystander CPR, which may cause bias in the results. Poor CPR quality may decrease survival in patients with OHCA . Such information is essential for a more precise evaluation of the effectiveness of legislation.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, this study cannot control for unrecorded variables, such as the quality of bystander CPR, which may cause bias in the results. Poor CPR quality may decrease survival in patients with OHCA . Such information is essential for a more precise evaluation of the effectiveness of legislation.…”
Section: Discussionmentioning
confidence: 99%
“…ediatric in-hospital cardiac arrest (IHCA) affects approximately 15,000 children annually with current survival to hospital discharge (SHD) of 30-40% (1). Improvements over time in survival and functional outcomes after IHCA can be attributed to numerous factors, an important one being the establishment of cardiopulmonary resuscitation (CPR) quality metrics, which includes: compression rate and depth, chest wall recoil, chest compression fraction, degree of ventilation, and hemodynamic-directed CPR (HD-CPR) (2)(3)(4)(5). HD-CPR requires the presence of invasive monitoring for continuous arterial blood pressure and noninvasive monitoring of end-tidal Co 2 (etco 2 ).…”
mentioning
confidence: 99%
“…HD-CPR requires the presence of invasive monitoring for continuous arterial blood pressure and noninvasive monitoring of end-tidal Co 2 (etco 2 ). Established targets for HD-CPR have been incorporated into resuscitation guideline recommendations (2,3,5).…”
mentioning
confidence: 99%
“…Last, Yates et al (1) report no association between ET co 2 measurements, available in 35 patients, and survival with favorable neurologic outcome among the ICU-RESUS ECPR cohort. In a recent publication of the entire ICU-RESUS cohort (234 patients), Morgan et al (14) found that average ET co 2 greater than or equal to 20 mm Hg during CPR was associated with improved survival to hospital discharge but was also not associated with favorable neurologic outcome. There was a high prevalence of CHD in the ICU-RESUS ECPR cohort with 85% diagnosed with CHD, compared with 66% cardiac medical or surgical patients in analysis by Morgan et al (14).…”
mentioning
confidence: 99%
“…In a recent publication of the entire ICU-RESUS cohort (234 patients), Morgan et al (14) found that average ET co 2 greater than or equal to 20 mm Hg during CPR was associated with improved survival to hospital discharge but was also not associated with favorable neurologic outcome. There was a high prevalence of CHD in the ICU-RESUS ECPR cohort with 85% diagnosed with CHD, compared with 66% cardiac medical or surgical patients in analysis by Morgan et al (14). Indeed, the ICU-RESUS cohort included 12 infants with interstage SV physiology, four with BDG, nine patients with systemic to pulmonary artery shunt.…”
mentioning
confidence: 99%